DIAGNOSIS KEBANGKRUTAN BISNIS (Studi Kasus Pelaku Bisnis Mobil Bekas Di Semarang) - Totok Wibisono; Aprih Santoso (Universitas Semarang, 2017)
Bankruptcy can be defined as a situation where the company is experiencing lack or insufficiency of funds to run or continue his efforts. Sometimes bankruptcy is also defined as a state or a situation where the company fails or no longer able to meet obligations to creditors .. This study is a qualitative research, data collection method using linear snowball method, where researchers gather information about the used car businesses in Semarang bankrupt. Interview rolled like a snowball because it must be interviewed one by one informant with persuasive way in order to dig important information about some of the causes of bankruptcy they experienced. The results of this study explains that the majority of defaults caused by the use of capital structure which is not qualified, followed by lack of proper accounting reporting, subsequent poor management systems, and the last of the economic factor. Limitations of this study is, on the informant that focuses on the used car business only, and has not been tested for other businesses. This research is expected to provide benefits for businesses, because a business must have a system of early prevention against bankruptcy.